Identification of the ~3.55 keV emission line candidate objects across the sky - Savchenko, D.O.; Iakubovskyi, D.A. (Advances in Astronomy and Space Physics, 2015)
An emission line at the energy ∼3.55 keV detected in different galaxies and galaxy clusters has caused numerous discussions in high-energy astrophysics and particle physics communities. To reveal the origin of the line, we analyzed publicly-available observations of MOS cameras from XMM-Newton cosmic observatory - the instrument with the largest sensitivity for narrow faint X-ray lines - previously combined in X-ray sky maps. Because an extremely large timescale is needed for detailed analysis, we used the wavelet method instead. Extensive simulations of the central part of the Andromeda galaxy are used to check the validity of this method. The resulting list of wavelet detections now contains 235 sky regions. This list will be used in future works for more detailed spectral analysis.